Alpha-synuclein phosphorylation controls neurotoxicity and inclusion formation in a Drosophila model of Parkinson disease. - Chen, L.; Feany, M.B. (Nature Neuroscience, 2005)
Alpha-synuclein is phosphorylated at serine 129 (Ser129) in intracellular protein aggregates called Lewy bodies. These inclusion bodies are the characteristic pathologic lesions of Parkinson disease. Here we define the role of phosphorylation of Ser129 in alpha-synuclein toxicity and inclusion formation using a Drosophila model of Parkinson disease. Mutation of Ser129 to alanine to prevent phosphorylation completely suppresses dopaminergic neuronal loss produced by expression of human alpha-synuclein. In contrast, altering Ser129 to the negatively charged residue aspartate, to mimic phosphorylation, significantly enhances alpha-synuclein toxicity. The G protein-coupled receptor kinase 2 (Gprk2) phosphorylates Ser129 in vivo and enhances alpha-synuclein toxicity. Blocking phosphorylation at Ser129 substantially increases aggregate formation. Thus Ser129 phosphorylation status is crucial in mediating alpha-synuclein neurotoxicity and inclusion formation. Because increased number of inclusion bodies correlates with reduced toxicity, inclusion bodies may protect neurons from alpha-synuclein toxicity.